Nanodiscs Incorporating Native β1 Adrenergic Receptor as a Novel Approach for the Detection of Pathological Autoantibodies in Patients with Dilated Cardiomyopathy. (19th November 2019) - Sun, Ruoyu; Mak, Stefanie; Haschemi, Jafer; Horn, Patrick; Boege, Fritz; Luppa, Peter B
Abstract: Background: Dilated cardiomyopathy (DCM) is a common cause of heart failure with high morbidity and mortality rates. The association of anti-β1 adrenergic receptor (β1AR) autoantibodies with disease progression was shown by various studies and in vivo animal experiments. The prevalence of these disease-driving autoantibodies was estimated as 25% to 75% in DCM. The removal of autoantibodies or the interruption of their action leads to a prolonged improvement of heart function. However, presence and impact of the autoimmune aspect in DCM patients must be examined for targeted treatment. Methods: We developed a heterogeneous immunoassay to support the diagnosis of anti-β1AR autoantibody-induced DCM. The presentation of the native conformational epitope was enabled by reconstitution of human β1AR into lipid bilayer nanodiscs, which stabilize the incorporated receptor in aqueous solution for measurements with standard immunological techniques. Results: The incorporation of β1AR into nanodiscs was verified by chromatographic, spectroscopic, and immunological methods. The functionality was shown by interaction assays with appropriate binding partners. Furthermore, β1AR nanodiscs were applied to immunoassays for the detection of anti-β1AR in human sera. Surface plasmon resonance spectroscopy and ELISA were developed, optimized, and validated. The optimized β1AR nanodisc ELISA enabled a simultaneous measurement of 40 samples in duplicate. An interassay variance of 24% and an intraassay variance of 5% were determined. The limit of detection and the limit of quantification were determined as 0.64 ng/mL and 1.26 ng/mL, respectively (related to a monoclonal anti-β1AR). Conclusions: Nanodisc technology is suitable as a novel biomimetic membrane system to stabilize and present β1AR for detection of autoantibodies with immunological methods in DCM patients.